2021
DOI: 10.1038/s41467-021-24735-z
|View full text |Cite
|
Sign up to set email alerts
|

Lsm12 is an NAADP receptor and a two-pore channel regulatory protein required for calcium mobilization from acidic organelles

Abstract: Nicotinic acid adenine dinucleotide phosphate (NAADP) is a potent Ca2+-mobilizing second messenger which uniquely mobilizes Ca2+ from acidic endolysosomal organelles. However, the molecular identity of the NAADP receptor remains unknown. Given the necessity of the endolysosomal two-pore channel (TPC1 or TPC2) in NAADP signaling, we performed affinity purification and quantitative proteomic analysis of the interacting proteins of NAADP and TPCs. We identified a Sm-like protein Lsm12 complexed with NAADP, TPC1, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 40 publications
1
53
1
Order By: Relevance
“…YM201636 has anti-viral activity 32,40 , and TPC2 also matters for virus entry 30,32 signaling, it can also be activated by other mechanisms, e.g., by NAADP via Lsm12 for TPC-mediated Ca 2+ mobilization 18 . Therefore, direct blockade of TPC2 by YM201636 can have a more profound effect than that caused by a reduction in PI (3,5)P2 synthesis via inhibition of PIKfyve activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…YM201636 has anti-viral activity 32,40 , and TPC2 also matters for virus entry 30,32 signaling, it can also be activated by other mechanisms, e.g., by NAADP via Lsm12 for TPC-mediated Ca 2+ mobilization 18 . Therefore, direct blockade of TPC2 by YM201636 can have a more profound effect than that caused by a reduction in PI (3,5)P2 synthesis via inhibition of PIKfyve activity.…”
Section: Discussionmentioning
confidence: 99%
“…The endolysosomal TPCs regulate the function of the endolysosomal system, including endomembrane dynamics and Ca 2+ homeostasis of the acidic stores 3,11 . Accumulating evidence supports that TPCs are critical to NAADP-evoked Ca 2+ release from acidic stores 1,[12][13][14][15][16][17][18] . TPCs are involved in many cellular processes, including autophagy 19 , migration and proliferation of cancer cells 20,21 , muscle cell differentiation 22 and contraction 16 , and fertilization 23 , and they are implicated in pigmentation [24][25][26] , Parkinson's disease 27 , and fatty liver disease 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that other NAADP binding proteins exist and participate in NAADP signalsome. Zhang et al have identified Lsm12 as a high affinity NAADP binding protein that is essential for NAADP -induced TPC2 activation (54). The Lsm12 data suggest that NAADP signaling has more components that need to be identified and studied.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Additionally, a previous study by Zhang et al. also identified LSM12 as an NAADP receptor essential for NAADP-evoked TPC activation and Ca2 + transportation from intracellular acidic stores ( 11 ). The oncologic roles of LSM family members have also been identified in several tumor types ( 12 14 ).…”
Section: Introductionmentioning
confidence: 97%